Multifunctional electrolyte for lithium metal battery and application of multifunctional electrolyte
By using tetrahydropyran, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1,3-dioxolane in the lithium metal battery electrolyte, the problem of performance decay of the electrolyte under high and low temperature conditions is solved, and the efficient operation and long cycle performance of the battery at extreme temperatures is achieved.
Patent Information
- Application Number
- CN202510191867.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The existing lithium metal battery electrolyte exhibits problems such as decreased conductivity, solidification, and decomposition under high and low temperature conditions, resulting in battery performance attenuation and safety hazards.
Three ether solvents, tetrahydropyran, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1,3-dioxolane, are used in conjunction with the bilithium salt to form a multifunctional electrolyte, improving the solvation structure and interface stability of the electrolyte.
It significantly improves the working performance and cycle stability of lithium metal batteries at high and low temperatures, ensures that the battery can maintain excellent performance at extreme temperatures, and is perfectly compatible with high voltage positive electrode materials, broadening the scope of battery application.
Smart Images

Figure CN119890454A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of high and low temperature electrolytes for lithium metal batteries, and relates to a multifunctional electrolyte for lithium metal batteries and applications thereof, and in particular to a multifunctional electrolyte for high and low temperature lithium metal batteries and applications thereof. Background Art
[0002] Since the commercialization of secondary batteries, the demand for high-energy-density batteries has continued to rise. Among them, lithium metal batteries, with their unparalleled high-energy-density characteristics, have shown great potential to lead the trend of battery technology innovation, and are expected to promote leapfrog progress in electric vehicles, consumer electronics and even the energy storage industry. However, the current commercial carbonate electrolyte system dominated by ethylene carbonate (EC) has exposed significant technical bottlenecks when facing high and low temperature application scenarios, especially extreme low and high temperature conditions. Under low temperature conditions, the conductivity of the electrolyte system drops sharply, and even solidifies, which directly leads to a significant attenuation of the battery capacity; under high temperature conditions, it faces the challenges of accelerated electrolyte decomposition and increasingly violent interfacial reactions, which in turn cause safety hazards, seriously restricting the performance and application promotion of lithium metal batteries under these extreme conditions.
[0003] At present, exploring and developing high-performance electrolyte systems suitable for high and low temperature environments has become the key to promoting the further development of lithium metal battery technology. In extremely low or high temperature environments, the electrolyte will experience a series of problems that affect battery performance and safety, such as increased viscosity, decreased conductivity, electrolyte volatilization, and electrolyte decomposition. Ether electrolytes have the advantages of low viscosity, high conductivity, good fast charging and low temperature application, which can effectively improve the application of lithium metal batteries in high and low temperature environments. However, ether electrolytes also have problems such as volatility, instability, strong reactivity with lithium and low electrochemical stability. Especially under high voltage conditions, the ether molecules in the electrolyte may be decomposed by electrolysis, further affecting the performance of the battery.
[0004] Therefore, developing a lithium metal battery electrolyte that can be adapted to high-voltage positive electrode materials and ensure stable performance at high and low temperatures is of great significance for promoting the in-depth development of lithium metal battery electrolyte technology. Summary of the invention
[0005] In view of the deficiencies in the prior art, the first object of the present invention is to provide a multifunctional electrolyte for lithium metal batteries. The electrolyte has low viscosity, low freezing point and good thermal stability through the coordinated use of three specific ether reagents and dilithium salts. At the same time, the electrolyte not only has good compatibility with the negative electrode of the lithium metal battery, but can also adapt to high-voltage positive electrode materials.
[0006] The second purpose of the present invention is to provide an application of a multifunctional electrolyte for lithium metal batteries. The application of the electrolyte to lithium metal batteries significantly improves the working performance of lithium metal batteries under extreme temperature conditions, especially for high and low temperature lithium metal batteries. The electrolyte / electrode interface stability can be improved under high and low temperature environments, and the working temperature of the battery can be widened, so that the lithium metal battery still has excellent long cycle performance under high and low temperature conditions. At the same time, the electrolyte is perfectly compatible with high voltage positive electrode materials, which greatly broadens the application scope of lithium metal batteries.
[0007] In order to achieve the above technical objectives, the present invention provides a multifunctional electrolyte for a lithium metal battery, comprising a lithium salt and an organic solvent, wherein the organic solvent is composed of tetrahydropyran, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1,3-dioxolane in a volume ratio of (2.5-7):(2.5-7):(1-3); the lithium salt is composed of lithium bis(fluorosulfonyl)imide and lithium perchlorate in a molar ratio of (0.5-4):(0.5-4).
[0008] The reason why the electrolyte of the present invention can operate efficiently in high and low temperature environments is that it uses ether solvents to replace traditional carbonate solvents (such as EC, DMC). Ether solvents, with their shorter molecular chains and excellent fluidity, ensure that high conductivity can be maintained even under cold conditions, while showing significant advantages such as low melting point, low viscosity and high cost-effectiveness. However, for lithium metal batteries, when a single ether solvent is used, the surge in lithium ion coordination sites can easily cause solvent decomposition, hindering the discharge process, especially when used with high-voltage positive electrode materials. To solve this problem, the present invention cleverly uses three ether solvents for use in combination, among which tetrahydropyran and 1,3-dioxolane are cyclic structure ether compounds, while 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is a linear ether solvent. By using a cyclic ether solvent, its weak solvation characteristics can be utilized, which can greatly promote Li +The interaction between the anion and the anion is conducive to the decomposition of the anion at the electrode interface, and by introducing the linear ether of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether into the cyclic ether solvent system, not only the appropriate amount of lithium ion coordination sites is ensured to maintain efficient ion conduction, but also the melting point and viscosity of the electrolyte are further reduced, so as to perfectly adapt to the high-voltage positive electrode material and show excellent electrochemical performance under high and low temperature environments. In addition, the 1,3-dioxolane used in the electrolyte system of the present invention undergoes a ring-opening polymerization reaction under the induction of lithium salts, and rapidly polymerizes on the inorganic two-dimensional solid electrolyte interface (SEI) to form an upper organic-lower inorganic composite SEI film layer, wherein the lower inorganic SEI has a high mechanical strength, which can avoid the rupture and failure of the SEI film, and the upper organic SEI film is insoluble in organic solvents, which can effectively prevent the co-embedding of solvent molecules, greatly improving the stability of the electrode material, thereby enhancing the capacity and cycle life of the battery.
[0009] The inventors found that compared with other common cyclic ether solvents, tetrahydropyran has a six-membered ring structure, which gives it higher chemical stability and reduces the by-products produced by solvent decomposition. When it is used in combination with 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, the cycle life of the battery can be extended and the safety can be improved.
[0010] The key to the technical solution of the present invention is to control the volume ratio of tetrahydropyran, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1,3-dioxolane to be (2.5-7): (2.5-7): (1-3). In the present invention, tetrahydropyran and 1,3-dioxolane are both cyclic ethers. By controlling the amount of these two and the amount of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, when applied to lithium metal batteries (especially lithium cobalt oxide batteries), the problem of excessive viscosity of the electrolyte at low temperatures can be effectively improved, and the weak solvation characteristics of the solvent can be further reduced, which can greatly reduce the Li +The interaction between the electrolyte and the solvent further reduces the occurrence of side reactions of the solvent at the interface; if the amount of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is too small (that is, when the amount of cyclic ether solvents in the electrolyte is too high), due to the poor oxidation resistance of the cyclic ether itself, oxidative decomposition will occur on the positive electrode side under high voltage, thereby adversely affecting the performance of the lithium metal battery; and when the amount of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is too large, the surge in lithium ion coordination sites can easily induce solvent decomposition and hinder the discharge process. In addition, if the dosage of 1,3-dioxolane is too high, the 1,3-dioxolane monomer will be triggered by the lithium salt to undergo a ring-opening polymerization reaction, rapidly polymerize and prevent it from further dissolving, resulting in limited dissolution of the lithium salt, seriously affecting and reducing the ionic conductivity of the electrolyte, and the uneven electrolyte formed by the polymerization will further deteriorate the electrode interface; when the dosage of 1,3-dioxolane is too low, it will cause the stability of the lithium metal battery to deteriorate during high and low temperature cycles; and when the dosage of tetrahydropyran is too low, it is not conducive to the decomposition of anions at the electrode interface to form a solid inorganic SEI layer, resulting in a decrease in electrode strength and stability; and when the dosage of tetrahydropyran is too high, due to the problem of excessive viscosity of tetrahydropyran at low temperatures, it will hinder the migration of lithium ions in the electrolyte, resulting in a slow ion conduction rate, and will also cause the polarization phenomenon of the battery to intensify during the charge and discharge process, further aggravating the attenuation of battery performance. More preferably, the volume ratio of tetrahydropyran, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1,3-dioxolane is (6-7):(2.5-3):(2-3).
[0011] As a preferred solution, the lithium salt is composed of lithium bis(fluorosulfonyl)imide and lithium perchlorate in a molar ratio of (0.5-4): (0.5-4). The present invention uses lithium bis(fluorosulfonyl)imide and lithium perchlorate in synergistic use to form a solid electrolyte layer rich in LiF and LiCl on the positive electrode side of the battery, which can effectively prevent the ether organic solvent of the present invention from contacting the positive electrode material, reduce the occurrence of side reactions under high and low temperature operation, thereby protecting the positive electrode material and improving the cycle stability of the battery. Within the molar ratio range selected by the present invention, it has the best effect of reducing side reactions. It is further preferred that the lithium salt is composed of lithium bis(fluorosulfonyl)imide and lithium perchlorate in a molar ratio of (3-4): (0.5-1).
[0012] As a preferred solution, the total concentration of the lithium salt in the electrolyte is 0.1-4 mol / L. When the lithium salt concentration is too low, the lithium ion conductivity will be low, resulting in poor low-temperature performance of the lithium-ion battery. When the concentration is too high, the viscosity of the electrolyte will be too high, affecting the migration speed of lithium ions at low temperatures. It is further preferably 0.1-1.5 mol / L, and even more preferably 0.8-1.5 mol / L.
[0013] As a preferred solution, the electrolyte further comprises at least one of phosphate compounds, fluorocarbonate compounds, borate compounds, sulfite compounds, sultone compounds and ether compounds.
[0014] The present invention also provides an application of a multifunctional electrolyte, which is applied to high and low temperature lithium metal batteries. The present invention mainly combines the weak solvation characteristics of the main solvent tetrahydropyran, which can greatly promote the + The interaction between the anions and the electrolyte helps the decomposition of the anions at the electrode interface to form a solid inorganic SEI layer; the co-solvent 1,3-dioxolane is conducive to the formation of an organic SEI coating layer on the inorganic SEI layer and an organic-inorganic composite SEI layer at the electrode interface; the co-solvent 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether can significantly improve the antioxidant properties of the electrolyte. At the same time, it has an extremely low freezing point (-94.27°C) and a high boiling point (93.17°C), which allows the electrolyte to remain liquid in an extremely wide temperature range, and has good low-temperature stability, thermal stability and chemical stability. The synergistic effect of the three improves the stability of the electrolyte / electrode interface under high and low temperature environments, so that the lithium metal battery still has excellent long-cycle performance at high and low temperatures, and can be stably charged and discharged at a wide operating temperature of over 100°C. At the same time, the perfect compatibility of the electrolyte with high-voltage positive electrode materials has greatly broadened the application scope of lithium metal batteries.
[0015] As a preferred solution, the lithium metal battery includes a positive electrode plate, a negative electrode plate and a separator.
[0016] As a preferred solution, the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer arranged on the positive electrode current collector; the active material of the positive electrode active material layer is lithium cobalt oxide or lithium nickel cobalt manganese oxide; it is further preferred that the active material of the positive electrode active material layer is lithium cobalt oxide. When used as a low-temperature positive electrode material, due to its unique layered structure, it has the advantages of high operating voltage, low self-discharge, superior electrochemical performance, and stable structure compared to other positive electrode materials. Compared with other electrolytes, the electrolyte of the present invention can be more adapted to the high voltage window of lithium cobalt oxide.
[0017] As a preferred solution, the active material of the negative electrode plate is lithium metal or lithium alloy.
[0018] As a preferred solution, the lithium alloy includes at least one of Li-Zn alloy, Li-Zn-O alloy, Li-Sn alloy, Li-Sn-O alloy, Li-Mg alloy and Li-Al alloy.
[0019] The invention discloses a method for preparing a multifunctional electrolyte for lithium metal batteries, comprising: mixing lithium salt, tetrahydropyran, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1,3-dioxolane in an inert gas atmosphere, and then stirring the mixture with a magnetic bar for 30 to 45 minutes to obtain the electrolyte.
[0020] Compared with the prior art, the beneficial technical effects brought by the technical solution of the present invention are as follows:
[0021] (1) The electrolyte of the present invention effectively improves the solvation structure of the electrolyte through the synergistic effect of tetrahydropyran, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1,3-dioxolane, greatly reduces the viscosity of the electrolyte and improves the conductivity of the electrolyte at high and low temperatures, so that lithium ions can be quickly transported in the electrolyte and have a faster desolvation process. At the same time, in the electrolyte system of the present invention, 1,3-dioxolane and tetrahydropyran can also construct an organic-inorganic composite SEI film layer, wherein the inorganic SEI of the lower layer has a high mechanical strength, which can avoid the rupture and failure of the SEI film, and the organic SEI film of the upper layer is insoluble in organic solvents, which can effectively prevent the co-embedding of solvent molecules, greatly improving the stability of the electrode material, thereby enhancing the capacity and cycle life of the battery.
[0022] (2) The electrolyte provided by the present invention is applied to high and low temperature lithium metal batteries, and can stably charge and discharge at a wide operating temperature range of over 100°C. In addition, in low temperature environments, lithium metal batteries can maintain a relatively high discharge specific capacity and cycle stability, significantly improving the low temperature performance of lithium metal batteries; in normal temperature environments, lithium metal batteries can achieve stable cycling at a high voltage of 4.45V, and can also achieve 10C ultra-high rate charge and discharge, significantly improving the high voltage performance and rate performance of lithium metal batteries.
[0023] (3) The present invention uses two specific organic-inorganic lithium salts and an organic solvent in a coordinated manner to form a solid electrolyte layer rich in LiF and LiCl on the positive electrode side of the battery, which can effectively prevent the ether electrolyte of the present invention from contacting the positive electrode material, reduce the occurrence of side reactions under high and low temperature operation, thereby protecting the positive electrode material and improving the cycle stability of the battery.
[0024] (4) The electrolyte provided by the present invention can adapt to high-voltage positive electrode materials.
[0025] (5) The raw materials of the electrolyte of the present invention are simple and easy to obtain, the production cost is low, and it has the potential for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1The cycle performance diagram of the lithium cobalt oxide full battery assembled in Example 2 is charged to 4.45V at 0.5C constant current at 30°C, and then discharged to 2.5V at 0.5C constant current.
[0027] Figure 2 Rate performance diagram of the lithium cobalt oxide full battery assembled in Comparative Examples 1-2 and Example 2 at 30°C with a voltage range of 2.5-4.35V.
[0028] Figure 3 The cycle performance diagram of the lithium cobalt oxide full battery assembled in Example 2 at 30°C with a voltage range of 2.5~4.35V and at an ultra-high rate of 6C.
[0029] Figure 4 The long cycle performance diagram of the lithium cobalt oxide full battery assembled for Comparative Examples 1-2 and Example 2 at a low temperature of -40°C, charged to 4.45V at a constant current of 0.05C, and discharged to 2.5V at a constant current of 0.1C, wherein the data of Comparative Examples 1 and 2 overlap.
[0030] Figure 5 The long cycle performance diagram of the lithium cobalt oxide full battery assembled in Comparative Examples 1-2 and Example 2 at a high temperature of 55°C, charged to 4.45V at a constant current of 0.5C, and discharged to 2.5V at a constant current of 0.5C.
[0031] Figure 6 This is a discharge curve diagram of the lithium cobalt oxide full battery assembled in Example 2 working at over 100°C. DETAILED DESCRIPTION
[0032] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0034] In the embodiments of the present invention, unless otherwise specified, the chemical reagents used can be purchased or prepared by existing preparation methods, and the instruments and equipment used are conventional equipment in the prior art.
[0035] Example 1
[0036] The electrolyte of this embodiment is composed of lithium salt and organic solvent. The lithium salt is lithium bis(fluorosulfonyl)imide and lithium perchlorate (LiClO4). The total concentration of lithium salt is 1 mol / L, and the molar ratio of the two lithium salts is 4:1. The organic solvent is composed of tetrahydropyran, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and the volume ratio of the three solvents is 2.5:3:7. In an inert gas atmosphere, the lithium salt and the organic solvent are mixed and stirred for 30 minutes to obtain an electrolyte after mixing evenly.
[0037] Example 2
[0038] The electrolyte of this embodiment is composed of lithium salt and organic solvent. The lithium salt is lithium bis(fluorosulfonyl)imide and lithium perchlorate. The total concentration of lithium salt is 1 mol / L, and the molar ratio of the two lithium salts is 4:1. The organic solvent is composed of tetrahydropyran, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether. The volume ratio of the three solvents is 7:3:2.5. In an inert gas atmosphere, the lithium salt and the organic solvent are mixed and stirred for 30 minutes to obtain an electrolyte after mixing evenly.
[0039] Example 3
[0040] The electrolyte of this embodiment is composed of a lithium salt and an organic solvent. The lithium salt is lithium bis(fluorosulfonyl)imide and lithium perchlorate. The lithium salt concentration is 1 mol / L, and the molar ratio of the two lithium salts is 4:1. The organic solvent is composed of tetrahydropyran, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and the volume ratio of the three solvents is 4.75:3:4.75. In an inert gas atmosphere, the lithium salt and the organic solvent are mixed and stirred for 30 minutes to obtain an electrolyte after mixing evenly.
[0041] Example 4
[0042] The electrolyte of this embodiment is composed of lithium salt and organic solvent. The lithium salt is lithium bis(fluorosulfonyl)imide and lithium perchlorate. The total concentration of lithium salt is 1 mol / L, and the molar ratio of the two lithium salts is 4:1. The organic solvent is composed of tetrahydropyran, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether. The volume ratio of the three solvents is 4.375:1.875:6.25. In an inert gas atmosphere, the lithium salt and the organic solvent are mixed and stirred for 30 minutes to obtain an electrolyte after mixing evenly.
[0043] Comparative Example 1
[0044] The electrolyte of this comparative example is a commercial conventional electrolyte (LB-515), which is composed of lithium salt and organic solvent. The lithium salt is lithium hexafluorophosphate, and the lithium salt concentration is 1 mol / L. The organic solvent is composed of ethylene carbonate, ethyl methyl carbonate and fluoroethylene carbonate, and the volume ratio of the three solvents is 3:7:1. In an inert gas atmosphere, the lithium salt and the organic solvent are mixed and stirred for 30 minutes to obtain an electrolyte after mixing evenly.
[0045] Comparative Example 2
[0046] The electrolyte of this comparative example is composed of a lithium salt and an organic solvent. The lithium salt is lithium bis(fluorosulfonyl)imide and lithium perchlorate. The total concentration of the lithium salt is 1 mol / L, and the molar ratio of the two lithium salts is 4:1. The organic solvent is tetrahydropyran. In an inert gas atmosphere, the lithium salt and the organic solvent are mixed and stirred for 30 minutes to obtain an electrolyte after the mixture is evenly mixed.
[0047] Comparative Example 3
[0048] The only difference between this comparative example and Example 2 is that 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is not added to the organic solvent, and the other steps and conditions are the same.
[0049] Comparative Example 4
[0050] The difference between this comparative example and Example 2 is that the organic solvent is changed to tetrahydropyran and 1,3-dioxolane in a volume ratio of 1:1, and the other steps and conditions are the same.
[0051] Comparative Example 5
[0052] The difference between this comparative example and Example 2 is that the organic solvent is changed to tetrahydropyran and 1,3-dioxolane in a volume ratio of 3:7, and the other steps and conditions are the same.
[0053] Comparative Example 6
[0054] The difference between this comparative example and Example 2 is that the organic solvent is changed to 1,3-dioxolane, and the other steps and conditions are the same.
[0055] Comparative Example 7
[0056] The only difference between this comparative example and Example 2 is that the organic solvent is replaced by tetrahydropyran, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether in a volume ratio of 1.75:0.75:10, and the other steps and conditions are the same.
[0057] Comparative Example 8
[0058] The difference between this comparative example and Example 2 is that tetrahydropyran is replaced by an equal volume of linear ether ethylene glycol dimethyl ether, and the other steps and conditions are the same.
[0059] Performance Test:
[0060] Raman spectra of the electrolyte were collected using a Raman microscope under a 532nm excitation laser and the FSI in the Raman spectrum was recorded. - Anion peak (Raman shift 775cm -1 The Raman shift deviation value of the position is shown in Table 1.
[0061] NMR was used to detect the solvation structure in the electrolyte. 5 mg samples of different solutions and electrolytes were dissolved in CDCl3-d in glass tubes for further testing to detect whether polymers appeared in the solvent.
[0062]
[0063] From the results in Table 1, it can be seen that when the volume of tetrahydropyran solvent is appropriately reduced, no polymer will appear in the electrolyte, and FSI - The absolute value of the peak shift value gradually decreases, indicating that FSI - Anion and Li + The binding ability of the solvent and Li is enhanced, making it easier to form a stable and strong SEI film at the interface. + The combination of tetrahydropyran and organic solvent is weakened, which reduces the decomposition of solvent at the interface, improves the cycle performance and rate performance of the battery, and enhances the safety of the battery. However, if the volume of tetrahydropyran in the organic solvent is too small, polymers will appear.
[0064] Using a conductivity meter, the electrolyte was placed in a 30°C constant temperature box for 1 hour before conducting a conductivity test and recording the conductivity value. The results are shown in Table 2.
[0065]
[0066] From the results in Table 2, it can be seen that when the co-solvent 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is gradually added, since it is a non-polar solvent and does not dissolve lithium salts, the lithium ion concentration in the electrolyte decreases, resulting in a decrease in ionic conductivity. Therefore, only by adding an appropriate amount of linear ether can the conductivity be guaranteed to be higher than that of conventional commercial electrolytes.
[0067] The electrochemical performance of the LCO / Li half-cell prepared using the electrolyte of the above embodiment was tested using the Xinwei battery testing system.
[0068] High-voltage charge and discharge experiment: The battery obtained in the example was placed in a 30°C constant temperature box for 12 hours, then charged to 4.45V at 0.1C, and then discharged to 2.5V at 0.1C constant current, and the charge and discharge capacity under high voltage was recorded. The results are shown in Table 3.
[0069]
[0070] As shown in Table 3, it can be seen from Comparative Examples 2 to 6 and 8 that when the volume ratio of tetrahydropyran is small, 1,3-dioxolane will undergo ring-opening polymerization under the addition of lithium bis(fluorosulfonyl)imide, and high cut-off voltage charge and discharge test cannot be achieved. As shown in Comparative Example 8 and Example 2, when replaced with isovolumetric linear ether glycol dimethyl ether, charge and discharge performance test cannot be achieved at high cut-off voltage. This is because tetrahydropyran has a more stable six-membered ring structure and stronger antioxidant capacity than glycol dimethyl ether. At the same time, tetrahydropyran can provide lower weak solvation energy and low interface impedance. As shown in Example 2 and Comparative Example 2, when the solvent is completely replaced with tetrahydropyran, it will also have an adverse effect on high-voltage performance. This is because the oxidation stability of tetrahydropyran itself is relatively poor and it is easy to decompose on the positive electrode side, thereby affecting the high-voltage performance of the battery.
[0071] Figure 1 This is the long cycle performance diagram of the LCO|Li full battery assembled in Example 2 at 30°C and 4.45V high voltage. After 200 cycles, the capacity retention rate reaches 90.7%.
[0072] High rate performance experiment: The battery obtained in the example was placed in a 30° C. constant temperature box for 12 hours and then subjected to a constant current charge and discharge test, with the test voltage range being 2.5 to 4.35 V.
[0073] Figure 2 The rate performance diagram of the LCO|Li full battery assembled in Comparative Examples 1-2 and Example 2 at 30°C shows that at an ultra-high rate of 20C, the capacity is still 93.4mAh / g, with a capacity retention rate of 64.3% at 0.1C charge and discharge. However, the commercial electrolytes of Comparative Examples 1 and 2 have significantly lower capacities than Example 2 at an ultra-high rate of 20C.
[0074] Figure 3 This is the specific capacity-voltage diagram of the LCO|Li full battery assembled in Example 2 at 30°C and 6C rate. After 400 cycles, the capacity is still 100.4 mAh / g.
[0075] Low temperature performance experiment: The batteries obtained in Comparative Examples 1-2 and Example 2 were activated at room temperature, then placed in a low temperature box, left to stand at -40°C for 2 hours, charged at 0.05C constant current to 4.45V, and then discharged at 0.1C constant current to 2.5V for cycle testing.
[0076] Figure 4 The figure is a cycle performance diagram of the LCO|Li full battery assembled in Comparative Examples 1-2 and Example 2 at -40°C. After 100 cycles, the full battery made of the electrolyte of Example 2 of the present invention still has a capacity of 76.8 mAh / g, and the capacity retention rate is 80%; however, the full batteries made of the commercial electrolytes of Comparative Examples 1 and 2 cannot operate at low temperatures.
[0077] High temperature performance experiment: The batteries obtained in Comparative Examples 1-2 and Example 2 were activated at room temperature, then placed in a high temperature box, left to stand at 55°C for 2 hours, charged at 0.5C constant current to 4.3V, and then discharged at 0.5C constant current to 2.5V for cycle testing.
[0078] Figure 5 The figure is a cycle performance diagram of the LCO|Li full battery assembled in Comparative Examples 1-2 and Example 2 at 55°C. After 100 cycles, the full battery made of the electrolyte of Example 2 of the present invention still has a capacity of 153.5 mAh / g, and the capacity retention rate is 90%, which is significantly higher than that of Comparative Examples 1 and 2.
[0079] High and low temperature discharge performance experiment: The battery obtained in Example 2 was activated at room temperature and the room temperature capacity was tested. It was then placed in a thermostat at different temperatures. After standing for 2 hours at the tested temperature, it was discharged at a constant current of 0.1C to 2.5V, and the discharge capacity and voltage diagrams at different temperatures were recorded.
[0080] Figure 6 This is the discharge capacity-voltage diagram of the LCO|Li full battery assembled in Example 2 at -50~55°C. The battery can work normally at a wide temperature range of over 100°C.
[0081] It can be seen from the above electrochemical test results that the battery prepared by the electrolyte of the present invention has better high-voltage performance, room temperature rate, high and low temperature performance and more stable cycle performance. The coordinated use of double lithium salts to form a solid electrolyte layer rich in LiF and LiCl on the positive electrode side of the battery can effectively prevent the electrolyte from contacting the positive electrode material, reduce the occurrence of side reactions under high and low temperature operation, thereby protecting the positive electrode material and improving the cycle stability of the battery. The addition of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1,3-dioxolane effectively improves the solvation structure of the electrolyte, greatly reduces the viscosity of the electrolyte and improves the conductivity of the electrolyte at high and low temperatures, so that lithium ions can be quickly transmitted in the electrolyte and have a faster desolvation process. In summary, the electrolyte combination method of the present invention improves the voltage window of ether solvents and the transmission rate of lithium ions at high and low temperatures, improves the electrode interface compatibility, and enables the battery to achieve stable charging and discharging at a wide operating temperature of more than 100°C.
[0082] In summary, the present invention effectively improves the ionic conductivity of the electrolyte, improves the high and low temperature performance and fast charging performance of the lithium metal battery, and realizes the role of a multifunctional electrolyte through the synergistic effect between cyclic ether organic solvents, linear ether organic solvents and lithium salts.
[0083] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A multifunctional electrolyte for a lithium metal battery, comprising a lithium salt and an organic solvent, characterized in that: The organic solvent is composed of tetrahydropyran, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1,3-dioxolane in a volume ratio of (2.5-7): (2.5-7): (1-3); The lithium salt is composed of lithium bis(fluorosulfonyl)imide and lithium perchlorate in a molar ratio of (0.5-4):(0.5-4).
2. A multifunctional electrolyte for lithium metal batteries according to claim 1, characterized in that: The total concentration of the lithium salt in the electrolyte is 0.1-4 mol / L.
3. A multifunctional electrolyte for lithium metal batteries according to claim 1 or 2, characterized in that: The electrolyte further comprises at least one of a phosphate compound, a fluorocarbonate compound, a borate compound, a sulfite compound, a sultone compound and an ether compound.
4. The use of a multifunctional electrolyte for lithium metal batteries according to any one of claims 1 to 3, characterized in that: The electrolyte is applied to high and low temperature lithium metal batteries.
5. The use of a multifunctional electrolyte for lithium metal batteries according to claim 4, characterized in that: The lithium metal battery comprises a positive electrode sheet, a negative electrode sheet and a separator; The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector; The active material of the positive electrode active material layer is lithium cobalt oxide or lithium nickel cobalt manganese oxide; The active material of the negative electrode plate is lithium metal or lithium alloy.
Citation Information
Patent Citations
Electrolyte for lithium-sulfur battery, and lithium-sulfur battery comprising same
CN108292782A
Low-temperature electrolyte for local weak solvation lithium metal battery
CN118572193A
Electrolyte, battery and electric device
CN119452496A
Electrolyte solution for lithium ion secondary battery, and lithium ion secondary battery
JP2018170110A
KR20210115319A